2006
DOI: 10.1111/j.1464-410x.2006.06574.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of anticholinergics in men with lower urinary tract symptoms suggestive of benign prostatic hyperplasia: a systematic review and meta‐analysis

Abstract: OBJECTIVETo assess the safety and efficacy of anticholinergics in men with lower urinary tract symptoms (LUTS) suggestive of benign prostatic hyperplasia (BPH) by a systematic review of published reports and a meta-analysis of the reported outcomes. METHODSWe searched Medline, Embase and Cochrane databases , and hand-searched relevant reference lists and conference proceedings, for studies on the use of anticholinergics in men with BPH or bladder outlet obstruction. Eligible studies were assessed for quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…A key safety consideration in the use of antimuscarinics in elderly men is the possible risk of inducing increased PVR/urinary retention. A meta-analysis showed an incidence of urinary retention while antimuscarinic treatment in men of 0.8% [29]. In line with previous controlled studies with propiverine [12, 13, 18], the observed changes in PVR were small and acute urinary retention occurred only rarely in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…A key safety consideration in the use of antimuscarinics in elderly men is the possible risk of inducing increased PVR/urinary retention. A meta-analysis showed an incidence of urinary retention while antimuscarinic treatment in men of 0.8% [29]. In line with previous controlled studies with propiverine [12, 13, 18], the observed changes in PVR were small and acute urinary retention occurred only rarely in the present study.…”
Section: Discussionsupporting
confidence: 89%
“…studies provide compelling evidence that antimuscarinic + α‐blocker treatment provides significant benefit to men with LUTS including OAB symptoms (19–21,25,37,42), and several prospective studies have also demonstrated that an antimuscarinic + α‐blocker is more effective for OAB symptoms than an α‐blocker alone in men (26–28,39). These findings are consistent with a meta‐analysis of data from five randomised trials and 15 observational studies that included men with LUTS suggestive of BPO (51), which found that antimuscarinics improved IPSS scores, particularly storage scores, and generally had a positive effect on HRQL. These findings are important because the storage symptoms that define OAB are common and bothersome in men and adversely affect HRQL, perhaps to a greater extent than voiding symptoms (12,52,53).…”
Section: Discussionsupporting
confidence: 86%
“…Although our findings parallel what has previously been described in other systematic reviews, 22 the only meta-analysis to date only quantified changes in PVR, Qmax and urodynamic parameters. 23 Furthermore, it predates the majority of the RCTs that we have incorporated into our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%